2014
DOI: 10.1038/srep04736
|View full text |Cite
|
Sign up to set email alerts
|

Real-time single-cell imaging of protein secretion

Abstract: Protein secretion, a key intercellular event for transducing cellular signals, is thought to be strictly regulated. However, secretion dynamics at the single-cell level have not yet been clarified because intercellular heterogeneity results in an averaging response from the bulk cell population. To address this issue, we developed a novel assay platform for real-time imaging of protein secretion at single-cell resolution by a sandwich immunoassay monitored by total internal reflection microscopy in sub-nanolit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
98
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(101 citation statements)
references
References 30 publications
3
98
0
Order By: Relevance
“…The mechanisms underlying pyroptosis are unknown, but appear to initially involve the appearance of caspase-1-dependent plasma membrane pores of 1.1-2.4 nm diameter [27], followed by dissipation of ionic gradients, cell swelling, and osmotic lysis. A number of studies have highlighted the temporal association of IL-1b secretion and cell lysis [15,28,29], promoting a model in which IL-1b is passively released during cell lysis. This was most recently proposed from studies in which cytokine secretion from single cells was monitored in real-time by total internal reflection fluorescence microscopy [28,29].…”
Section: Cell Deathmentioning
confidence: 99%
See 2 more Smart Citations
“…The mechanisms underlying pyroptosis are unknown, but appear to initially involve the appearance of caspase-1-dependent plasma membrane pores of 1.1-2.4 nm diameter [27], followed by dissipation of ionic gradients, cell swelling, and osmotic lysis. A number of studies have highlighted the temporal association of IL-1b secretion and cell lysis [15,28,29], promoting a model in which IL-1b is passively released during cell lysis. This was most recently proposed from studies in which cytokine secretion from single cells was monitored in real-time by total internal reflection fluorescence microscopy [28,29].…”
Section: Cell Deathmentioning
confidence: 99%
“…A number of studies have highlighted the temporal association of IL-1b secretion and cell lysis [15,28,29], promoting a model in which IL-1b is passively released during cell lysis. This was most recently proposed from studies in which cytokine secretion from single cells was monitored in real-time by total internal reflection fluorescence microscopy [28,29]. The authors highlighted the tight temporal coupling of IL-1b release and loss of plasma membrane integrity, and showed that cell lysis is the ultimate fate of IL-1b-producing monocyte/macrophages.…”
Section: Cell Deathmentioning
confidence: 99%
See 1 more Smart Citation
“…To create a cell-friendly microenvironment, microwell arrays are typically composed of biocompatible materials such as PDMS (49)(50)(51), PEG (52,53), collagen (54), agarose (55), or silicon (56). PDMS, collagen, and agarose-based microarrays can be fabricated via soft lithography approaches.…”
Section: Microwellsmentioning
confidence: 99%
“…Recently, a microfabricated platform was developed for real-time detection of cytokine secretion using total internal reflection fluorescence microscopy (50). IL-1β secreted from stimulated human peripheral blood monocytes was monitored at 1 minute intervals, demonstrating cell-tocell heterogeneity in the onset of cytokine secretion.…”
Section: Detecting Cytokine Secretionmentioning
confidence: 99%